2016
DOI: 10.5009/gnl15584
|View full text |Cite
|
Sign up to set email alerts
|

PMK-S005 Alleviates Age-Related Gastric Acid Secretion, Inflammation, and Oxidative Status in the Rat Stomach

Abstract: Background/AimsThe aim of this study was to evaluate the effect of the synthetic S-allyl-l-cysteine (SAC) PMK-S005 on gastric acid secretion, inflammation, and antioxidant enzymes in aging rats.MethodsThe rats were divided into four groups at 31 weeks of age and were continuously fed a diet containing a vehicle control, PMK-S005 (5 or 10 mg/kg), or lansoprazole (5 mg/kg). Gastric acid secretion and connective tissue thickness of the lamina propria were evaluated at 74 weeks and 2 years of age. Tumor necrosis f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…The significant increase in gastric mucosal expression of TNF-α in aged CRS group compared to adult CRS group suggests the finding that the stomach in aged rats is exposed to more susceptible condition of inflammations than younger age. Similar results were found in a previous study which indicated that protein expressions of TNF-α and interleukin-1β (IL-1β) in the gastric mucosa were increased with age [5]. Another study demonstrated that chronic inflammation is considered as an important risk factor underlying aging and age-related diseases [3].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The significant increase in gastric mucosal expression of TNF-α in aged CRS group compared to adult CRS group suggests the finding that the stomach in aged rats is exposed to more susceptible condition of inflammations than younger age. Similar results were found in a previous study which indicated that protein expressions of TNF-α and interleukin-1β (IL-1β) in the gastric mucosa were increased with age [5]. Another study demonstrated that chronic inflammation is considered as an important risk factor underlying aging and age-related diseases [3].…”
Section: Discussionsupporting
confidence: 86%
“…Previous studies have documented several important abnormalities including changes in the structural and functional properties of the gastric mucosa and GI tract in aged people [3,5]. It has been disclosed that aging is an independent risk factor for the development of NSAIDinduced gastric ulceration [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, calcium carbonate, the most commonly used form, requires gastric acid to be digested due to its poor solubility in water [12]. Tis may lead to indigestion for people of insufcient gastric acid excretion such as kids and the aged [13].…”
Section: Introductionmentioning
confidence: 99%